Applying Odds of Soft Computing-based Approaches for Environmental Impact Assessment - Tulbure, Ildiko (Recent Progress in Science and Technology Vol. 8, 2023)
Diverse human activities, as industrial, agricultural, commercial, and touristic ones have the direct goal to support increasing humanity quality of life. Anyway, it has been remarked that beside positive direct and desired effects of these activities, simultaneously they can have also negative, undesired, and sometimes unthinkable effects on environment and society. For assuring the sustainable development of human society is therefore necessary to assess economic activities not only from economic and technological points of view but also from environmental and social ones. In this context appropriate indicators for economic, environmental, and social aspects must be developed and used. To carry out environmental impact assessments environmental indicators on local and regional level are to be used. General notions regarding environmental indicators will be presented, their usage possibilities as well as application examples from practical situations. Possibilities to define in a modular way environmental indicators will be debated and emphasised. A fuzzy logic-based aggregation method will be presented for a concrete situation of assessing air pollution on regional level, and by this the advantages of using soft computing methods will be pointed out. Obtained results will be debated, and conclusions regarding the usage potential of presented methodology will be drawn.